Differential Item Functioning and Implications for Testing in Nigeria Education System - Yinusa Akintoye Faremi; Kasali Jimoh (Indonesian Journal of Learning Education and Counseling, 2022)
The study analyzes and assesses differential item functioning (DIF) by different demographic groups, particularly gender and cultural groupings, in order to produce appropriate test items. It is essential to examine the extent to which test items work differently among subgroups when selecting test items. This paper is based on modern ways for removing irrelevant parameters and sources of bias of any kind so that a test can produce valid results. As a result, it is recommended that test developers and policymakers evaluate and exercise caution in fair test practice by devoting more effort to more unbiased test development and decision-making. In educational testing, examination bodies should employ the Item Response Theory, and test developers should be aware of test items that may induce bias in response patterns between male and female students or any other sub-group of interest.